Antiretroviral Drug Detection in a Community-Randomized Trial of Universal HIV Testing and Treatment: HPTN 071 (PopART). (31st October 2022) - Fogel, Jessica M; Zewdie, Kidist; Clarke, William A; Piwowar-Manning, Estelle; Breaud, Autumn; Moore, Ayana; Kosloff, Barry; Shanaube, Kwame; van Zyl, Gert; Scheepers, Michelle; Floyd, Sian; Bock, Peter; et al.
Abstract: Background: Antiretroviral therapy (ART) reduces human immunodeficiency virus (HIV) transmission risk. The primary aim of this study was to evaluate ART uptake in a trial in Zambia and South Africa that implemented a community-wide universal testing and treatment package to reduce HIV incidence. Methods: Study communities were randomized to 3 arms: A, combination-prevention intervention with universal ART; B, combination-prevention intervention with ART according to local guidelines; and C, standard of care. Samples were collected from people with HIV (PWH) during a survey visit conducted 2 years after study implementation: these samples were tested for 22 antiretroviral (ARV) drugs. Antiretroviral therapy uptake was defined as detection of ≥1 ARV drug. Resistance was evaluated in 612 randomly selected viremic participants. A 2-stage, cluster-based approach was used to assess the impact of the study intervention on ART uptake. Results: Antiretroviral drugs were detected in 4419 of 6207 (71%) samples (Arm A, 73%; Arm B, 70%; Arm C, 60%); 4140 (94%) of samples with ARV drugs had viral loads <400 copies/mL. Drug resistance was observed in 237 of 612 (39%) viremic participants (95 of 102 [93%] with ARV drugs; 142 of 510 [28%] without drugs). Antiretroviral therapy uptake was associated with older age, female sex, enrollment year, seroconverter status, and self-reported ART (all P < .001). The adjusted risk ratio for ART uptake was similar for Arm A versus C (1.21; 95% confidence interval [CI], .94–1.54; P = .12) and Arm B versus C (1.14; 95% CI, .89–1.46; P = .26). Conclusions: At the 2-year survey, 71% of PWH were on ART and 94% of those participants were virally suppressed. Universal testing and treatment was not significantly associated with increased ART uptake in this cohort. Abstract : Antiretroviral therapy uptake was evaluated in HPTN 071 (PopART). Over 70% of people with HIV were on ART after 2 years of study implementation. Universal testing and treatment was not significantly associated with increased ART uptake in this cohort.